Tuesday

July 22, 2014

July 22, 2014

Posted by **Larry** on Thursday, March 27, 2008 at 8:13pm.

(g o f)(x):f(x)=x-3/6, g(x)=6x+3

g(f(x))

g(x-3/6)

=6*x-3+3/6

would my answer be: (g o f)(x)=x

I am not sure if I answered the problem completely.

- Algebra -
**bobpursley**, Thursday, March 27, 2008 at 8:32pmYes, you did it correctly.

**Related Questions**

algebra functions - can someone please check my answer For each problem, ...

algebra functions check my answer - For each problem, construct two composite ...

algebra functions - construct two composite functions, Evaluate each composite ...

functions - For each problem, construct two composite functions, . Evaluate each...

Composite Functions - Find the composite functions for the given functions. (6 ...

algebra functions - can someone help me with this and explain it to me step by ...

Functions - consider the functions g(x)=(4-x^2)^0.5 and h(x)=(x^2)-5. find the ...

math - how would this equation look: y=f(x+3) when y=f(x)= x^2 would it look ...

Biology - PLEASE CONSIDER EACH OF THE FOLLOWING CHANGES SEPARATELY. Be sure to ...

math - how to you find a composite function form of y in this problem? y = 1/[(x...